Originally Posted by

**DHS1** Hey all. I have this problem:

$\displaystyle x=c_{1}e^x+c_2e^{-x}$

I am supposed to use this to find out what $\displaystyle c_1$ and $\displaystyle c_2$ are:

$\displaystyle y(0)=1$

$\displaystyle y'(0)=2$

What happens when I use the first equation is I get

$\displaystyle 1=c_{1}e^0+c_2e^{-0}$

$\displaystyle 1=c_{1}(1)+c_2(1)$

$\displaystyle 1=c_{1}+c_2$

leaving me know way to solve for them. The answer in the back of the book says:

$\displaystyle y=\frac{3}{2}e^x-\frac{1}{2}e^{-x}$

Can anyone show me what I should do? If this one is answered, I will be able to complete all the other problems. Because I'm getting stuck on the same thing, having 1 equation and 2 variables $\displaystyle c_1$ and $\displaystyle c_2$

Thanks,

DHS1